Concomitant variants in NF1, LZTR1 and GNAZ genes probably contribute to the aggressiveness of plexiform neurofibroma and warrant treatment with MEK inhibitor. Issue 5 (20th December 2021) - Cohen‐Barak, Eran; Toledano‐Alhadef, Hagit; Danial‐Farran, Nada; Livneh, Ido; Mwassi, Banan; Hriesh, Maysa; Zagairy, Fadia; Gafni‐Amsalem, Chen; Bashir, Husam; Khayat, Morad; Warrour, Nassim; Sher, Osnat; et al.
Abstract: Neurofibromatosis 1 (NF1) is caused by germline mutations in the NF1 gene and manifests as proliferation of various tissues, including plexiform neurofibromas. The plexiform neurofibroma phenotype varies from indolent to locally aggressive, suggesting contributions of other modifiers in addition to somatic loss of NF1 . In this study, we investigated a life‐threatening plexiform neurofibroma in a 9‐month‐old female infant with NF1. Germline mutations in two RASopathy‐associated genes were identified using whole‐exome sequencing—a de novo pathogenic variant in the NF1 gene, and a known pathogenic variant in the LZTR1 gene. Somatic analysis of the plexiform neurofibroma revealed NF1 loss of heterozygosity and a variant in GNAZ, a gene encoding a G protein‐coupled receptor. Cells expressing mutant GNAZ exhibited increased ERK 1/2 activation compared to those expressing wild‐type GNAZ. Taken together, we suggest the variants in NF1, LZRT1 and GNAZ act synergistically in our patient, leading to MAPK pathway activation and contributing to the severity of the patient's plexiform neurofibromatosis. After treatment with the MEK inhibitor, trametinib, a prominent clinical improvement was observed in this patient. This case study contributes to the knowledge of germline and somatic non‐NF1 variants affecting the NF1 clinical phenotype and supports use of personalized, targeted therapy.